The Steroid Hormone 20-Hydroxyecdysone Regulates the Conjugation of Autophagy-Related Proteins 12 and 5 in a Concentration and Time-Dependent Manner to Promote Insect Midgut Programmed Cell Death - Li, Yong-Bo; Yang, Ting; Wang, Jin-Xing; Zhao, Xiao-Fan (Frontiers in Endocrinology, 2018)
Autophagy requires the conjugation of autophagy-related protein 12 (ATG12) to autophagy-related protein 5 (ATG5) through covalent attachment. However, the signals regulating ATG12–ATG5 conjugation are unclear. The larval midgut of lepidopteran insects performs autophagy and apoptosis sequentially during the transition of larvae to pupae under regulation by the steroid hormone 20-hydroxyecdysone (20E), thus representing a model to study steroid hormone regulation of ATG12–ATG5 conjugation. In the present study, using the lepidopteran insect Helicoverpa armigera as a model, we report that 20E regulates the conjugation of ATG12–ATG5 in a concentration and time-dependent manner. The ATG12–ATG5 conjugate was abundant in the epidermis, midgut, and fat body during metamorphosis from the larvae to the pupae; however, the ATG12–ATG5 conjugate level decreased at the time of pupation. At low concentrations (2–5 µM) over a short time course (1–48 h), 20E promoted the conjugation of ATG12–ATG5; however, at 10 µM and 72 h, 20E repressed the conjugation of ATG12–ATG5. ATG12 was localized in the larval midgut during metamorphosis. Knockdown of ATG12 in larvae caused death with delayed pupation, postponed the process of midgut programmed cell death (PCD), and repressed ATG8 (also called LC3-I) transformation to LC3-II and the cleavage of caspase-3; therefore, knockdown of ATG12 in larvae blocked both autophagy and apoptosis. Knockdown of ATG12 in H. armigera epidermis cell line cells also repressed 20E-induced autophagosome formation and caspase-3 activation. The results suggested that 20E plays key role in the regulation of ATG12–ATG5 conjugation in a concentration and time-dependent manner for autophagy or apoptosis, and that ATG12 is necessary by both autophagy and apoptosis during insect midgut PCD.